Assessment of social, demographic determinants and oral hygiene practices in relation to dental caries among the children attending Anganwadis of Hingna, Nagpur - Shweta Suresh Bhayade; Rakesh Mittal; Shweta Chandak; Ashish Bhondey (Wolters Kluwer Medknow Publications, 2016)
Background: In developing countries, dental caries is the most common disease of the early childhood. Its increased prevalence in younger age group have been predictive of oral health problems in future, affecting oral health and development leading to several morbid conditions of oral and general health. Prevalence and incidence of dental caries is highly influenced by a number of risk factors such as gender, age, socioeconomic status, dietary patterns, and oral hygiene habits. Aim: To assess social, demographic determinants and oral hygiene practices in relation to dental caries among the children attending Anganwadis of Hingna, Nagpur. Materials and Methodology: A cross sectional study in 27 Anganwadis of Hingna, Nagpur was carried out over a period of two months and a total of 324 subjects attending the Anganwadis were enrolled. Social, demographic and oral hygiene practices in relation to dental caries were assessed in the study population. Results: Out of 324 subjects, 206 had dental caries and 38 were found to be malnourished. A significant association was found among age, malnutrition, parent's educational status, oral hygiene practices, total number of siblings, and dental caries. Conclusion: Anganwadis should be addressed routinely on effective oral and general health promoting strategies which must include education of parents, oral and general health issues, risk factors for dental caries, and malnutrition in children below 5 years of age.